Comparative Efficacy of Cavotricuspid Isthmus Ablation in Sinus Rhythm Versus Typical Atrial Flutter - Lyuboslav Katov; Yannick Teumer; Alyssa Schlarb; Sonja Reiländer; Deniz Aktolga; Federica Diofano; Carlo Bothner; Wolfgang Rottbauer; Karolina Weinmann-Emhardt (Hearts)
Background: Cavotricuspid isthmus (CTI)-dependent atrial flutter (AFL) is the most common atrial macro-reentrant tachycardia, characterized by a typical ECG pattern (type I ECG). Often, tachycardia terminates before it can be confirmed by an electrophysiological study (EPS), necessitating CTI ablation in sinus rhythm (SR). This study aims to compare the success rate of CTI ablation in patients with type I ECG during SR versus ongoing CTI-dependent AFL, focusing on arrhythmia recurrence. Methods: We screened patients at Ulm University Heart Center from January 2010 to November 2020 with type I ECG who underwent CTI ablation. Patients were divided into two groups: those whose tachycardia terminated before EPS and underwent ablation in SR, and those with ongoing CTI-dependent AFL during EPS. CTI ablation was deemed complete when a bidirectional conductance block was achieved, confirmed after 30 min. Results: A total of 230 patients were included, all showing typical AFL in ECG recordings. Of these, 67 patients underwent ablation in SR, while 163 were ablated during ongoing AFL. The median follow-up time was 2.7 years. Recurrence of CTI-dependent AFL occurred in 8.3% of patients: 4.5% in the SR ablation group and 9.8% in the ongoing AFL group. Kaplan–Meier estimation showed similar efficacy for both methods regarding arrhythmia recurrence (log-rank p = 0.07). Conclusions: Our decade-long study indicates that CTI ablation during SR is as effective as ablation during ongoing CTI-dependent AFL in achieving long-term freedom from arrhythmia. This research supports the efficacy of both techniques in clinical settings, validating a widely practiced approach.